Partial Enumeration in the Dehra Dun Forest Division - Sahai, R. (Indian Forester, 1947)
This article describes in detail the method of partial enumerations by systematic parallel strips, 2 chains wide, followed by the working plan party, Debra Dun forest division, during 1946-47. 2. It begins with giving a summary of indications of the Silviculturist, Forest Research Institute, Dehra Dun,about the practical application of the system. It then describes the nature of the country where the work was done. 3. On gentle slopes 20 per cents enumerations were done in strips 2 chains wide and 10 chains apart. 4. Details are given about- (i) fixing the direction of the strips and showing these on the map. (ii) the instruments used. (iii) the strength and alignment of the enumeration gangs. (iv) closing of the enumeration books to get data for every acre, sub-compartment, or strip. (v) the rate of progress and the cost of enumeration. 5. Suggestions are made about- (i) using the enumeration data for plotting on the map to produce a picture of the growing stock. (ii) using the method while the enumeration work is in progress for(a) stock-mapping or checking of the stock-maps. (b) collecting other valuable information like state of regeneration, undergrowth, etc. 6. Two appendices are given. Appendix I gives detailed instructions to enumerators and to the officer in charge. Appendix II gives suggestions for the use of symbols on the map to show the result of enmerations. 7. The article concludes by recommending the use of the system for all those forests which are being worked intensively and which are on suitable terrain.